Lauryn Harper falls apart - Robinson, Shauna (Sourcebooks Landmark, an imprint of Sourcebooks, 2025)
"Lauryn Harper had a plan. A high achieving, perfectly constructed, five-year plan. But after a (totally blown out of proportion) mishap at work that plan is put to the test. As punishment for her mistake she is transferred to the Ryser Charity Department, a branch of her corporation that just so happens to be located in the hometown she abandoned long ago--the same hometown that her powerful corporation is responsible for running into the ground. Horrified at the thought of returning and facing those she left behind (one in particular keeps coming to mind), Lauryn quickly comes up with a new plan: impress her boss enough that she's briskly whisked back to her big city life. However, it soon becomes clear that sticking to plans isn't that simple, especially when her ex-best friend enters the charity department demanding they help revitalize the town by throwing the famous Greenstead Fall Festival. Confronted by her past wrongs, Lauryn immediately agrees to host the festival on Ryser's dime, but soon enough Lauryn is swept away in town hijinks, chaotic planning committees, and a second chance at a childhood friend that shows her why home isn't necessarily a place she has to run from." -- Amazon.com.